Sociodemographic factors and teaching method preferences among university academics: Implications for effective curriculum implementation (Journal of Applied Learning and Teaching, 2023)
This research examined sociodemographic factors and teaching methods preferences among university academics: implications for effective curriculum implementation. This study employed a quantitative survey design; 400 academics were sampled. A questionnaire was used to obtain data; descriptive statistics and chi square analysis were used to test research hypotheses. The percentage of academics who prefer various teaching techniques during lessons for efficient curriculum implementation differs significantly; there is no meaningful connection between gender, academic faculty, years of classroom instruction, and their preference for teaching methods. The project method, followed by experimentation and demonstration methods, which are more constructivist and allow students to participate in their classes actively, were recommended as tools for academics to use more frequently. Despite these outcomes, individual differences must be respected. Regardless of gender, it is recommended that institutions regularly hold professional development seminars and training sessions, encourage multidisciplinary collaboration among educators, and enhance mentoring programmes and platforms for less experienced educators. The intersection of variables, including gender, faculty type, and teaching experience, should be taken into account in a comprehensive approach to pedagogical enhancement. Institutions can be aware of the changing requirements and preferences of educators by establishing channels for academic feedback on teaching techniques and preferences.